1995
DOI: 10.1080/10407789508913767
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evaluation of Different Turbulence Models for Confined Impinging and Opposing Jet Flows

Abstract: A numerical investigation war carried ouf to predict and compare the fluid /tow and heat tmnsfer characteristics of two-dimenswnal turbulent confined impinging and opposing jet jlows. Five low-Rtyoldr-number k-E models and the standard high-ReynoI&-number model were used in the simulntion. The newly proposed Yap correction war also tested with low-Reyno&-number models in order to investigate its effect on the heat tmnsferpredierions for the impinging jet case. It war found that in some modek Pis correction imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
37
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 82 publications
(37 citation statements)
references
References 24 publications
0
37
0
Order By: Relevance
“…Hosseinalipour and Mujumdar [35] compared the one standard and five low Reynolds number (LRN) versions of k-turbulence models to predict the heat transfer characteristics of confined turbulent single impinging and opposing slot jet flows. They also applied the Yap correction [35] to improve the prediction of downstream heat transfer of impinging jets, indicating that some of the models worked; however, those improvements were quite limited. Tzeng et al [36] used one standard and seven LRN k-models to predict the heat transfer performance of multiple jets.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hosseinalipour and Mujumdar [35] compared the one standard and five low Reynolds number (LRN) versions of k-turbulence models to predict the heat transfer characteristics of confined turbulent single impinging and opposing slot jet flows. They also applied the Yap correction [35] to improve the prediction of downstream heat transfer of impinging jets, indicating that some of the models worked; however, those improvements were quite limited. Tzeng et al [36] used one standard and seven LRN k-models to predict the heat transfer performance of multiple jets.…”
Section: Introductionmentioning
confidence: 99%
“…Chatterjee and Deviprasath [32] demonstrated that the off-stagnation point maxima of Nusselt number are entirely a consequence of upstream flow development because of vorticity diffusion. Numerical investigation of heat transfer rate using various k-models [34][35][36][37] has been carried out. Hosseinalipour and Mujumdar [35] compared the one standard and five low Reynolds number (LRN) versions of k-turbulence models to predict the heat transfer characteristics of confined turbulent single impinging and opposing slot jet flows.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier numerical studies [13] have found some difficulties to correctly simulate simple impinging jets with standard k-ε turbulent model. This study follows a RANS approach combined with a k-ε model to describe in-cylinder turbulence.…”
Section: Turbulence Model Validationmentioning
confidence: 99%
“…In this paper, the penetration of the transient wall-impinging jet after impingement is defined as the summation of the impinging distance, L, and the radial distance, X, to which the jet has penetrated along the wall. The computed penetration for impinging jets is defined as the impinging distance plus the maximum radial distance where the fuel mass fraction reaches a cut-off value of 0.01 [13].…”
Section: Turbulence Model Validationmentioning
confidence: 99%